PERCEPÇÃO DOS USUÁRIOS NO BAIRRO CIDADE BAIXA - Silva, Michelle; Miron, Luciana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Understanding the needs and expectations of different groups of users in the urban space in a neighborhood scale represents an opportunity to promote more quality in the built environment. Thus, the objective of this article is to evaluate the quality of the Cidade Baixa neighborhood in Porto Alegre / RS, through the perception of its users. The methodology included the collection of data through questionnaires made available on the internet and applied personally to residents and merchants. Data analysis was performed through statistical frequency tests. The main results indicate that the group of merchants tends to have a more positive perception than the group of residents regarding the perception of coexistence, accessibility, appearance, environmental comfort, and safety.